2012
DOI: 10.1002/ejic.201101066
|View full text |Cite
|
Sign up to set email alerts
|

Crystal‐Phase‐ and Morphology‐Controlled Synthesis of Fe2O3 Nanomaterials

Abstract: Abstractα‐ and γ‐Fe2O3 nanorods have been prepared from a β‐FeOOH precursor that was obtained by aqueous‐phase precipitation of ferric chloride. The oxyhydroxide precursor had a rodlike shape with a diameter of 30–40 nm and a length of 400–500 nm. Calcination at 500 °C of the rod‐shaped oxyhydroxide in air yielded α‐Fe2O3 nanorods, whereas heating to reflux in polyethylene glycol (PEG) at 200 °C resulted in the formation of γ‐Fe2O3 nanorods. Both oxides inherited the rodlike morphology of the precursor but exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 58 publications
0
32
0
1
Order By: Relevance
“…As shown in Figure 2A, ZnO did not present reduction peaks, which was probably the result of complete dihydroxylation and high thermal stability [24,25]. There were three reduction peaks for the Fe 2 O 3 : the first reduction peak below 400 • C was due to the reduction of Fe 2 O 3 to Fe 3 O 4 , while the broad peaks above 400 • C represented the further reduction of Fe 3 O 4 to metallic iron, perhaps through FeO [26,27]. All the mixed oxides showed different reduction behavior.…”
Section: Introductionmentioning
confidence: 95%
“…As shown in Figure 2A, ZnO did not present reduction peaks, which was probably the result of complete dihydroxylation and high thermal stability [24,25]. There were three reduction peaks for the Fe 2 O 3 : the first reduction peak below 400 • C was due to the reduction of Fe 2 O 3 to Fe 3 O 4 , while the broad peaks above 400 • C represented the further reduction of Fe 3 O 4 to metallic iron, perhaps through FeO [26,27]. All the mixed oxides showed different reduction behavior.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, Mou et al [2] reported that nano Fe 2 O 3 showed apparent crystal-phase effect in the reaction of NO reduction, and g-Fe 2 O 3 nanorod was more active than a-Fe 2 O 3 . Bau et al [3] also reported that uniform octahedral Cu 2 O showed higher activity in CO oxidation than cubic Cu 2 O.…”
Section: Introductionmentioning
confidence: 98%
“…In the latter spectrum, a new broad asymmetric band at ca. 560 cm À1 appears because of Fe-O stretching vibrations [53] which confirms the formation of c-Fe 2 O 3 inside the microspheres [54,55]. Moreover, there is a strong asymmetrical stretching band of carboxyl anion at 1585 cm À1 , which originates from the asymmetrical NH 3 + bending accompanied with a weak symmetrical 1533 cm À1 band of NH 3 + bending.…”
Section: Pegylated Magnetic Polymer Microspheres: Morphology Size Anmentioning
confidence: 51%